Dendroclimatic potential of red oak, Quercus sideroxyla (Fagaceae) in Mexico - Ortega-Arroyo, Edgar Jesús; Jiménez-Pérez, Javier; Villanueva-Díaz, Jose; Yerena-Yamallel, José Israel; Alanís-Rodríguez, Eduardo; Aguirre-Calderón, Oscar Alberto (Revista de Biología Tropical, 2021)
Introduction: Dendrochronological studies in Mexico have been mainly based on conifers, while hardwood species have been little studied. This has been the case of the genus Quercus, which has a high taxonomic diversity in the country but has not been previously studied for dendrochronological issues, despite the ecological and economic values of oak species. Objective: In the present investigation, the dendroclimatic potential of Quercus sideroxyla in Northwestern Mexico was determined, as well as its relationship with climatic variables such as precipitation and temperature. Methods: The research was carried out in the state of Durango, Chavarría Viejo with coordinates (23º43’ N & -105º33’ W). Samples of 5 cm to 7cm were collected in two sites under forest exploitation and processed by conventional dendrochronological techniques. Results: A chronology of total ring width was developed, which was composed of 30 samples from 16 trees for the period from 1917 to 2018 (101 years). Inter-series intercorrelation values of 0.43, mean sensitivity of 0.36, signal-to-noise ratio of 3.53 and first-order autocorrelation (0.58) were obtained. Regarding the climate-growth relationship, the ring width index values were correlated with data from the climatic station nearest to the study site, where winter-spring precipitation (January-May) was the variable with the greatest influence on the growth of the species. Conclusions: Based on the dendrochronological parameters, the high potential of the species that were used in dendroclimatic studies in the region has demonstrated that the response of the species to precipitation is similar to that of the conifers with which the Quercus sideroxyla shares its habitat with.